Modeling Psychological Well-being Based on Attachment Styles, Personality Traits, and Defense Mechanisms with the Mediation of Job Burnout in Emergency Medical Staff - Keshtkar, Mahboube; Aghayousfi, Alireza; Davoodi, Abdolvahid (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The aim of the present study was to model psychological well-being based on attachment styles, personality traits, and defense mechanisms with the mediation of job burnout in emergency medical staff. Methods and Materials: The research design was correlational using path analysis. The statistical population of this study included emergency medical staff in the southwest of Tehran Province (Islamshahr, Shahriar, Malard, Parand, Robat Karim) in 2023, with an approximate number of 450 individuals. For the selection of the research sample, 210 participants were chosen through purposive sampling based on Krejcie and Morgan’s table and the size of the statistical population. The participants completed the Psychological Well-being Scale (Ryff et al., 1989), the Revised Attachment Scale (Collins & Read, 1990), the Big Five Personality Traits Questionnaire (Goldberg, 1991), the Defense Style Questionnaire (Andrews et al., 1993), and the Maslach Burnout Inventory (Maslach, 1981). Data were analyzed using covariance analysis and path analysis with AMOS and SPSS 26. Findings: The results indicated that the path coefficient of the direct effect of attachment styles on predicting psychological well-being with the mediation of coping strategies in emergency medical staff was significant. It was also found that the path coefficient of defense mechanisms in predicting psychological well-being with the mediation of coping strategies in emergency medical staff was significant. Conclusion: Overall, it was determined that attachment styles and personality traits play a role in predicting psychological well-being with the mediation of job burnout in emergency medical staff.